The identity and taxonomic position of Pleias Kirkaldy, 1901 (Hemiptera: Heteroptera: Reduviidae: Emesinae) - Rédei, Dávid (Zootaxa, 2007)
Based on the examination of the holotype, Pleias ritsemae Kirkaldy, 1901 (Heteroptera: Reduviidae: Emesinae: Leistarchini), is redescribed and figured. No generic differences can be found between Pleias Kirkaldy, 1901 and Bagauda Bergroth, 1903, consequently the latter is a junior synonym of Pleias. Reversion to the senior name Pleias would require that the several nominal species currently included in Bagauda be transferred to the nominal genus Pleias. Therefore, in order to preserve stability, no nomenclatural changes are proposed in this paper, but an application has been submitted to the International Commission on Zoological Nomenclature to give Bagauda precedence over Pleias. Although congeneric, Pleias ritsemae is not conspecific with any other species currently in Bagauda and its differentiating characters are discussed. The following new synonymy is proposed: Ploiaria perfuga Miller, 1941, syn. n. = Pleias ritsemae Kirkaldy, 1901.